THE IMPACT OF VIRTUAL GAMES ON SOCIETY - Muhayyo Jalilova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article examines the impact of virtual games on society and explores the psychological, social, and personal effects of playing them. Virtual games have addressed issues related to community building, social influence and relationship management, personal relationships, and mental health. The article examines the impact of players' virtual gaming habits on their mental health and offers opportunities to reduce arousal, anxiety, or stress. However, we may add to your time by viewing it in a different window